Aplikasi Berbagai Marka Aromatik pada Varietas Padi Indonesia - Djarot Sasongko Hami Seno; Satya Nugroho; Tri Joko Santoso; Dimas Adrianto; Dewi Praptiwi; Aniversari Apriana; Zainal Alim Mas'ud (Jurnal Ilmu Pertanian Indonesia, 2011)
This research applied various badh2.7 and badh2.2 fragrant markers (Bradbury et al., 2005b, Lang and Buu 2008, Shi et al., 2008, Sakthivel et al., 2009) on popular Indonesia non-fragrant (Ciherang, Fatmawati) and fragrant (Pandan wangi, Rojo Lele, Mentik Wangi, Gunung Perak, Pulu mandoti, Pare Kembang, Sintanur) rice varieties. For comparison, IR64, Nippon bare and Taipei 309 were included. Rice DNA samples were isolated from young  leaves, and PCR amplified using each of those fragrant markers. Results using all badh2.7 markers were consistently supported the existence of 2 group badh2.7 mutation pattern, while the use of badh2.2 marker indicated that there was no ex on 2 mutation. Badh2.7 sequence analysis of non-fragrant Ciherang, and aromatik member of group 1 (Pandan Wangi), as well as group 2 (Mentik Wangi) showed different mutation pattern.